Developing a model for pre-action dispute resolution for strata dispute management in Malaysia - Mohamad, Nor Asiah (2015)
The Malaysian government has finally announced for the implementation of Strata Management Act 2013 with the aims to cater disputes in the management of strata titled properties. Among the most important aspect of the Act is to introduce Strata Management Tribunal as a platform to resolve disputes among the strata owners and all stakeholders in relation to strata management and maintenance. This research addresses the period prior to the adjudication process by the Tribunal and proposes a model for early dispute resolution before the hearing. The author argues that early dispute resolution or early conflict engagement is necessary despite the establishment of Strata Management Tribunal to address non-technical issues, which involve restoration of social relationship. The author highlights the practice of other jurisdiction, for example, Victoria, Australia as well Hong Kong. The findings of the research show that Alternative Dispute Resolution (ADR) methods such as mediation or conciliation are suitable to be adopted within and outside Tribunal process.